Pemanfaatan Sampah Plastik dengan Metode Ecobrick Sebagai Upaya Mengurangi Limbah Plastik - Majida, Andi Zulfa; Muzaki, Alif; Karomah, Khilyatul; Awaliyah, Megawati (Profetik: Jurnal Pengabdian Masyarakat, 2023)
Plastic waste is a pressing global issue that demands solution-oriented actions from various levels of society. Desa Kajen, Talang District, Tegal Regency, is no exception in facing the challenge of plastic waste. This article aims to explore the utilization of plastic waste through the Ecobrick method as an effort to reduce plastic waste in the village. The Ecobrick method involves compacting plastic waste into used plastic bottles, creating environmentally friendly bricks that can be used as an alternative building material. This study was conducted through a community engagement approach, involving active participation from the community of Desa Kajen. A preliminary study was conducted to identify the quantity and types of plastic waste generated and evaluate the level of community awareness regarding the negative impacts of plastic waste. Subsequently, awareness-raising and education were carried out to emphasize the importance of plastic waste management and the benefits of utilizing Ecobricks as a solution that they can independently undertake. In the implementation of this community engagement project, training and technical guidance were provided to ensure that the community could correctly and safely produce Ecobricks. Collaboration with the village government and local environmental organizations strengthened support and understanding of the significance of reducing plastic waste. Regular monitoring and evaluation were conducted to measure the program's impact and enhance its effectiveness. The results of this community engagement initiative showed an increase in community awareness about plastic waste and the benefits of using Ecobricks as an alternative solution. The community of Desa Kajen actively participated in producing Ecobricks and used them for various local development needs. Involvement of the village government and collaboration with relevant institutions opened opportunities for program expansion and the development of sustainable solutions.